PENGARUH PERSEPSI DAN PREFERENSI TAMU TERHADAP KEPUTUSAN MENGINAP DI HOTEL SYARIAH - Rifky Surya Irawan; Muhammad Yafiz; Mawaddah Irham (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research was conducted to determine perceptions and preferences regarding visitors' decisions when staying at the Grand Shaqillah Syariah Hotel Medan. Perception is an experience about objects, events, or relationships obtained by concluding information and interpreting messages, while preference is a concept, which is used in social sciences, especially economics or can be called tendencies. The data collection technique used was by distributing questionnaires. Classic assumption test, multiple linear regression analysis, as well as hypothesis testing using SPSS Version 26. The results of this study show that partially the Perception (X1) and Preference (X2) variables have a significant influence on visitors' decisions to stay at the Grand Shaqillah Syariah Hotel Medan with significant value <0.05. Then a significant value for perception was 0.045 and preference was 0.000. The partial influence of perception variables on visitors' decisions about staying overnight is 19.7%, preference variables are 36.4%. Simultaneously, the perception (X1) and preference (X2) variables have a significant effect on visitors' decisions to stay at the Grand Shaqillah Syariah Hotel Medan with a significant result of 0.000 < 0.5 and an influence of 22.1%.